2018
DOI: 10.3389/fchem.2018.00491
|View full text |Cite
|
Sign up to set email alerts
|

A New Mixed-Valence Mn(II)Mn(III) Compound With Catalase and Superoxide Dismutase Activities

Abstract: The synthesis, X-ray molecular structure, physico-chemical characterization and dual antioxidant activity (catalase and superoxide dismutase) of a new polymeric mixed valence Mn(III)Mn(II) complex, containing the ligand H2BPClNOL (N-(2-hydroxybenzyl)-N-(2-pyridylmethyl)[(3-chloro)(2-hydroxy)] propylamine) is described. The monomeric unit is composed of a dinuclear Mn(II)Mn(III) moiety, [Mn(III)(μ-HBPClNOL)(μ-BPClNOL)Mn(II)(Cl)](ClO4)·2H2O, 1, in which the Mn ions are connected by two different bridging groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 85 publications
3
14
0
Order By: Relevance
“…The electronic spectrum of 3 ( Supplementary Figure S10 ), collected in the region 800–200 nm in chloroform, is dominated by intense bands in the 235–300 nm UV range attributed to intra-ligand transitions and by a lower intensity band at 353 nm probably due to ligand–metal transitions. The Vis region shows a weak band at 464 nm, which could only be determined by analyzing a concentrated sample, attributed to d–d transitions compatible with a d 4 configuration of octahedral complexes of Mn(III) as reported in the literature [ 21 , 24 , 25 , 26 ]. The cyclic voltammetry carried out in a dichloromethane-based electrolyte, in agreement with AR Hendrickson et al [ 27 ], showed a quasi-reversible redox process (ratio of anodic and cathodic peak currents I p-ox /I p-red = 1.1; separation peaks ΔE = 140 mV) centered at +0.25 V vs. NHE relative to the pair Mn(III)/Mn(IV) ( Supplementary Figure S11 ).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The electronic spectrum of 3 ( Supplementary Figure S10 ), collected in the region 800–200 nm in chloroform, is dominated by intense bands in the 235–300 nm UV range attributed to intra-ligand transitions and by a lower intensity band at 353 nm probably due to ligand–metal transitions. The Vis region shows a weak band at 464 nm, which could only be determined by analyzing a concentrated sample, attributed to d–d transitions compatible with a d 4 configuration of octahedral complexes of Mn(III) as reported in the literature [ 21 , 24 , 25 , 26 ]. The cyclic voltammetry carried out in a dichloromethane-based electrolyte, in agreement with AR Hendrickson et al [ 27 ], showed a quasi-reversible redox process (ratio of anodic and cathodic peak currents I p-ox /I p-red = 1.1; separation peaks ΔE = 140 mV) centered at +0.25 V vs. NHE relative to the pair Mn(III)/Mn(IV) ( Supplementary Figure S11 ).…”
Section: Resultsmentioning
confidence: 81%
“…The ES is dominated by an intense band in the 235–300 nm UV range attributed to intra-ligand transitions and a lower intensity band at 355 nm probably due to ligand–metal transitions. In the Vis region, we observed a weak band at 498 nm and a shoulder at 606 nm, which could only be analyzed with the concentrated sample, attributed to d–d transitions compatible with the assumed configuration of pseudo-octahedral complexes [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the case of a polymeric mixed valence Mn( iii )/Mn( ii ) complex, Mn( iii )–O–Mn( iv ) was identified as an intermediate in a reaction with superoxide by EPR spectroscopy. 105 Our explicit observation of Mn( iv )-oxo intermediates generated from mononuclear Mn( ii ) SOD mimetics by CSI-MS, UV/vis and EPR spectra is unique. Using the SOD activity of the Zn( ii ) analogue of 2 ( 4 ) as an estimate for the ligand-only contribution to the reactivity, we conclude that the metal-based inner-sphere SOD mechanism provides the more efficient pathway for superoxide degradation in Mn-quinol/phenol-based systems.…”
Section: Discussionmentioning
confidence: 94%
“…Besides, the SOD activities of these Mn-Schiff base complexes are in the same range as for Mn-amine/pyridine complexes. 15,48…”
Section: Resultsmentioning
confidence: 99%
“…At higher complex concentration, the formation of a Mn(III)Mn(II) mixed valence complex is also possible through the nucleophilic attack of the Mn(III)-peroxo to the Mn(II) center of 6 . 48,63 The disappearance of the broad signal in the EPR spectra taken at long times suggests that the mixed valence dimer finally yields a homovalent one, probably a Mn(III) dimer.…”
Section: Resultsmentioning
confidence: 99%